In vivo Evidence for Partial Activation of Eosinophils via the Histamine H4-Receptor: Adoptive Transfer Experiments Using Eosinophils From H4R−/− and H4R+/+ Mice - Schirmer, Bastian; Bringmann, Luisa; Seifert, Roland; Neumann, Detlef (Frontiers in Immunology, 2018)
Our previous in vitro studies revealed that histamine via histamine the H4-receptors (H4R), as compared to other stimuli, such as eotaxin or formylpeptides, rather partially activates eosinophilic granulocytes (eosinophils). In order to evaluate the H4R-mediated activation of eosinophils in vivo, we employed dextran sodium sulfate (DSS)-induced colitis in mice, closely resembling human ulcerative colitis (UC), which is largely characterized by a local eosinophilic infiltration of the colon. IL-5-deficient BALB/c mice served as a model with reduced endogenous numbers of eosinophils, in which wild-type (H4R+/+) or H4R-deficient (H4R−/−) eosinophils were adoptively transferred during the course of DSS-induced colitis. During the 1-week observation period, transfer of eosinophils transiently reversed the acute clinical colitis-like phenotype (body weight loss, perianal bleeding, soft stool consistency) resulting from IL-5-deficiency. This reversion was significantly more pronounced upon transfer of eosinophils from H4R+/+ mice as compared to those from H4R−/− mice. Already at the end of the observation period, the clinical effects of the transfer of H4R+/+ and H4R−/− eosinophils became similar, as were the results of the histological examination of the cola and the analyses of cytokine production in cola and in re-stimulated lymph node cells performed at this time. Thus, analyzing clinical and pathological parameters representative of colitis in this model, we demonstrate that as well as in vitro, also in vivo histamine via the H4R only partially activates eosinophils.